Correlation of lithofacies and depositional environment using Markov chain analysis in Sambipitu formation at Ngalang river, Gunungkidul, Yogyakarta, Indonesia - Al Hussein Flowers Rizqi; Hendri Tri Purnomo (Sustinere: Journal of Environment and Sustainability, 2021)
The research area is located at Ngalang river, Gedangsari sub-district, Gunungkidul Regency, Special Region of Yogyakarta. The research area is part of southern mountain area which is composed of lithology of Sambipitu calcareous sandstone. The depositional process phase in the Sambipitu formation has a unique pattern and is relevant to the previous lithology. As a result, the stratigraphic position and lithological repetition pattern were reviewed using the statistical method (Markov chain). The aim of this research is to use geostatistics to examine the sedimentation trend in order to predict the existence of rock facies in the Sambipitu Formation. In each unit of lithology cycle, geostatistics is expected to assist, to predict and to interpret the significance of subsequent lithology appearances. The research method used was measured stratigraphy, determination of rock age and depositional environment based on fossil identification. In addition, this research used probability matrix in Markov chain analysis. The results of the Markov chain analysis showed that lithology of rock in the upper Sambipitu formation had a non-random transition pattern. The results of statistical calculation showed that the calculation value was greater than the Chi-square table value (333.9>34.38) that the H0 component was rejected. Lithofacies and depositional environment are correlated to several geological aspects such as distribution of rock facies, source of rock, paleobtahymetri, trace fossils and sedimentation process.